STUDY OF THE EFFECTIVENESS OF THE BIOLOGICALLY ACTIVE SUPPLEMENT "SOMNIUM" BASED ON MELATONIN - Nilufar Mukhutdinovna Rizaeva; Bobir Sabirovich Tulaganov; Iroda Shavkatovna Sharipova; Dildora Sembaevna Mirzakamalova (The Bioscan, 2024)
Among the numerous environmental factors that constantly affect the body, proper rational nutrition is one of the most important, as it ensures the preservation of life, health and human performance. The problem of rational nutrition is of particular importance in cases of various physiological and pathological overloads of the body. Unhealthy diet, both quantitatively and qualitatively, leads to the emergence of a number of different complications, such as at least 50% of cases of cardiovascular diseases, about 40% of cases of lung cancer, colon and rectum, kidneys, prostate, bladder in men and about 60% of cases of breast cancer, uterus, kidneys, intestines in women.